Knowledge and Attitudes of Protein Supplements Used Among Benghazi Gym Trainers - Elfarssi, Hameida; Ali, Nagwa; Eltegani, Tofaha; Othman, Murouj; Alobyde, Amani; Salheen, Afiyah (Libyan Journal of Public Health Practices, 2024)
Protein supplements are commonly utilized by everyone, from casual exercisers to highly skilled athletes, to enhance health and athletic performance. This study aimed to investigate the use of protein supplements among Benghazi gym users and examine their knowledge and attitudes toward protein supplement use. A cross-sectional study was conducted in a period between March and June 2023 at users of gyms in Benghazi, Libya. 240 participants in all, including 162 were males and 78 were females, were selected randomly from eight different gyms. A self-administered, validated, and pretested questionnaire was used. It contained items connected to personal information, the incidence, knowledge, attitudes, and practice of protein supplementation. The results showed that 68 % of respondents who took protein supplement were males and 32 % were females. They consumed between a scoop or two of supplements daily by 44.2% and 41% of participants took protein to maintain a good body shape. Coaches encouraged over 47.5% of the participants to use supplements containing protein. 68% of participants showed good knowledge and attitudes about protein supplement use and 77% of them were males and 23% were females. 50.4% of participants at fitness centers used the gym three times per week. Conclusions: in this research, individuals who used gyms showed positive attitudes and good understanding regarding taking protein supplements. There was also a significant correlation found between participants' daily protein calculations and their educational level.